The Application of Environmental Responsibility in Restaurant MSMEs in Bekasi Regency - Yunita Ismail Masjud; Ahmad - Solihin (President University, 2021)
In addition to the advancement of manufacturing industries, Bekasi Regency also has culinary as supporting industry. It is undeniable that culinary is indeed one of the mainstays of business in Indonesia. Seeing the other side of the culinary business, it turns out that the culinary business has a fairly serious risk to the environment. FAO (Food and Agriculture Organization) states that leftover food waste contributes 10% of the world emissions gas which causes greenhouse effects and other serious environmental impacts. The amount of risk caused by food waste is expected to be a concern and consideration for culinary businesses. So environmental damage is not getting bigger, and also can create a business that cares about the environment. To analyze the application of environmental awareness in restaurant MSMEs (Micro, Small, Medium Enterprises) in Bekasi Regency, this research using environmental responsibility variables as the dependent variable and independent variables namely environmental awareness, environmental accounting reporting and environmental audits. This study uses quantitative research methods that take primary data from 150 restaurant SMEs actors in Bekasi District. Analysis of data with multiple linear regression methods whose results show that environmental attention and environmental audit variables have no significant effect on the implementation of environmental responsibility, while the environmental accounting reporting variable has a significant effect on the implementation of environmental responsibility in restaurant SMEs in Bekasi District.